Blindness after laryngectomy and bilateral neck dissection in a diabetic patient: case report - Mamede, Rui Celso Martins (2001)
CONTEXT: Neck dissection that accompanies resection of the primary lesion in malignant tumors of the upper aerodigestive tracts may cause com- plications inherent to the procedure or to prolongation of surgical time, increasing the risks forthepatient.Amongthecomplicationsthatmight occur is blindness, a rare complication with only 10 cases reported in the literature thus far. OBJECTIVE: To present the case of a diabetic patient submitted totota llaryngectomy and modified and selective neck dissection that resulted in blindness. CASE REPORT: The authors report on a patient submitted to total laryngectomy and selective neck dissection on the left side, and modified radical neck dissection on the right, who developed blindness. This was probably due to intraoperative hypotension plus the contribution of decompensated diabetes mellitus and thrombosis of the internal jugular vein on the right side. The possible causes, risk factors and care to be taken to prevent this rare but highly debilitating complication are discussed.